Within‐population polymorphism of sex‐determination systems in the common frog (Rana temporaria). (25th May 2013) - Rodrigues, N.; Betto‐Colliard, C.; Jourdan‐Pineau, H.; Perrin, N.
Abstract: In sharp contrast with birds and mammals, the sex chromosomes of ectothermic vertebrates are often undifferentiated, for reasons that remain debated. A linkage map was recently published for Rana temporaria (Linnaeus, 1758) from Fennoscandia (Eastern European lineage), with a proposed sex‐determining role for linkage group 2 (LG2). We analysed linkage patterns in lowland and highland populations from Switzerland (Western European lineage), with special focus on LG2. Sibship analyses showed large differences from the Fennoscandian map in terms of recombination rates and loci order, pointing to large‐scale inversions or translocations. All linkage groups displayed extreme heterochiasmy (total map length was 12.2 cM in males, versus 869.8 cM in females). Sex determination was polymorphic within populations: a majority of families (with equal sex ratios) showed a strong correlation between offspring phenotypic sex and LG2 paternal haplotypes, whereas other families (some of which with female‐biased sex ratios) did not show any correlation. The factors determining sex in the latter could not be identified. This coexistence of several sex‐determination systems should induce frequent recombination of X and Y haplotypes, even in the absence of male recombination. Accordingly, we found no sex differences in allelic frequencies on LG2 markers among wild‐caught male and female adults, except in one high‐altitude population, where nonrecombinant Y haplotypes suggest sex to be entirely determined by LG2. Multifactorial sex determination certainly contributes to the lack of sex‐chromosome differentiation in amphibians.